PENGARUH MARKETING MIX TERHADAP PENINGKATAN PENJUALAN PADA USAHA CHEETOZ_SECOND DI KABUPATEN SIDENRENG RAPPANG - Muhammad Guntur, Andi; Muhammad Rusdi; Haslindah; Andi Riska Andreani Syafaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effect of the marketing mix on sales growth at Cheetoz_Second in Sidenreng Rappang Regency. The objectives of this research are to identify the implementation of the marketing mix strategy and to analyze its influence on sales growth. The study employed a quantitative approach with a descriptive-associative research design. The population consisted of 214 consumers, while the sample of 68 respondents was determined using the Slovin formula and selected through accidental sampling. Data were collected through observation, literature review, and questionnaires, and were analyzed using validity testing, reliability testing, normality testing, simple linear regression analysis, t-test, and the coefficient of determination (R²). The findings indicate that the implementation of the marketing mix strategy at Cheetoz_Second achieved an average percentage score of 92.7%, which falls into the very good category, indicating that the elements of product, price, place, promotion, people, process, and physical evidence have been implemented effectively. The simple linear regression analysis produced a regression coefficient of 0.921 with a significance value of 0.000 (<0.05), demonstrating that the marketing mix has a positive and significant effect on sales growth. Furthermore, the coefficient of determination (R²) of 0.910 indicates that 91% of the variation in sales growth is explained by the marketing mix, while the remaining 9% is influenced by other factors outside the scope of this study. Therefore, an effective implementation of the marketing mix has been proven to significantly improve sales performance at Cheetoz_Second and should be continuously optimized to strengthen business competitiveness and sustainability.